The Study of Using Introduction Themselves and Their Families Conversations in Teaching Speaking of 3rd Class Students of Elementary School - Pratiwi, Veronika Unun; Nurnaningsih, Nurnaningsih; Arianti, Arin (International Journal for Educational and Vocational Studies, 2019)
Speaking skills in English is a very important skill in general communication. This skill is needed even since school age children. SD Negeri Jombor 03 Bendosari Sukoharjo is located in Jombor sub-district, Bendosari sub-district, Sukoharjo regency, which has students with relatively low English speaking ability. This is evidenced from the document a student's grade is relatively lace that obtained by the researchers through observation.The purpose of this study is to provide convenience for students of SD Negeri Jombor 03 Bendosari Sukoharjo to improve their speaking skills, especially to introduce themselves and their families. The method used by researchers is practice individually, in pairs, and in groups. This method provides an opportunity for students to be more active and expressive to express ideas, and bring up peer tutors to reduce the tension or pressure that obtained indirectly in a foreign language learning. In addition to the planned method, researchers also made use of LCD media and letter cards along with plastic boards to help students more easily absorb the material. This media was contributed quite a lot.The students feel happy, enthusiastic and more expressive in accepting the material provided.The researchers obtained the data by  field observations, then the researchers made other instruments such as questionaire sheets, pretests and evaluations. The results of this study are quite significant. The students was increased by 30.66% than of the results of the pretest and posttest. This method is expected to be carried out elsewhere so that the benefits can be felt in the wider community.